Functionalized layered double hydroxide with compound to remove cationic and anionic pollutants: A review - Ishak, Siti Nabihan; Nizam Nik Malek, Nik Ahmad (Universitas Nahdlatul Ulama Surabaya, 2021)
Layered double hydroxide (LDH) is one of the promising clay minerals that show great potential in various applications owing to its versatile structural properties. Prominently known for its high anion exchange capacity, this allows LDH to be considered as one of the most effective adsorbents in removing anionic toxic. However, the structural property of LDH hinders it from removing cationic toxic. Therefore, LDH have been functionalized to enhance its adsorption properties. In the present work, we aim to summarize the recent progress of functionalized LDH with different compounds for removal of both anionic and cationic toxics. The adsorption isotherm and effect of pH on absorption capacity also have been briefly reviewed.